Evaluation Antibacterial Activity of Rosary Pea (Abrus precatorius L.) Leaf Extract against the Growth of Staphylococcus aureus and Shigella sonnei - Amalia Shari; Alda Bunga Syahfitri (Integrated Research and Testing Laboratory (LPPT) Universitas Gadjah Mada, 2026)
Bacteria are major contributors to infectious diseases, including Staphylococcus aureus and Shigella sonnei. Although antibiotics remain the primary treatment, prolonged use can lead to antimicrobial resistance, highlighting the need for alternative agents capable of inhibiting pathogenic bacteria. Scientific validation of medicinal plants is crucial for complementing traditional knowledge in bioprospecting efforts. The Rosary pea (Abrus precatorius L.) is one such plant with potential antibacterial properties. This study evaluates the inhibitory activity of Abrus precatorius L. leaf ethanol extract against S. aureus and S. sonnei at concentrations of 3.125%, 6.25%, 12.5%, 25%, 50%, and 100%. The extract demonstrated optimal activity at 100%, exhibiting moderate inhibition against S. aureus and weak inhibition against S. sonnei. These findings underscore the potential of Abrus precatorius L as a source of antibacterial compounds and provide a foundation for developing improved formulations with enhanced antibacterial efficacy.